Uninformed buyers and market efficiency - Carl G. Maier; Michal Marencak (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Empirical evidence shows that low cost of signaling interest in offers can result in a significant number of inappropriate signals. This paper provides a theoretical explanation for this observation as an equilibrium outcome of a model with utility maximizing fully rational agents that decide to signal their interest without knowing whether the offer suits them or not. We show that falling transaction costs can decrease market efficiency and social welfare.
Keywords: C72; D47; D83; E24; 330